Enhancing Students’ Critical Thinking in Physics through Discovery Learning-Based Worksheets: Integrating Facione’s Framework in a Quasi-Experimental Study - Susilawati Susilawati; Ananda Muliyana; Susanna Susanna (JURNAL PENDIDIKAN MIPA, 2026)
This study aims to investigate the effect of discovery learning-based student worksheets on improving students’ critical thinking skills in physics, particularly on the topic of straight motion. A quasi-experimental design with a non-equivalent control group was employed, involving 66 eleventh-grade students divided into an experimental group (n = 34) and a control group (n = 32), selected through purposive sampling. Data were collected using a set of 20 validated multiple-choice items designed to measure critical thinking skills. The results reveal that the experimental group achieved a higher mean posttest score (M = 75.64) compared to the control group (M = 71.91), with a moderate N-gain value (0.57). Statistical analysis using the independent samples t-test indicates a significant difference between the two groups (p = 0.01 < 0.05), confirming the effectiveness of the intervention. Notably, the highest improvement was observed in the inference indicator (91.18%), suggesting that the Discovery Learning approach particularly enhances students’ ability to draw logical conclusions. This study contributes an empirically-tested worksheet model that explicitly maps each discovery learning stage to a specific Facione critical thinking indicator. The differentiated N-Gain outcomes observed per indicator (ranging from 0.27 for self-regulation to 0.84 for inference) serve as empirical evidence of the mapping’s differential instructional effect, providing measurable diagnostic value beyond a holistic improvement score. It should be noted that the causal contribution of each individual worksheet stage to each specific indicator has not been directly tested; the observed differentiation represents a theoretically-grounded design inference supported by indicator-level outcome patterns. It is recommended that educators adopt discovery learning-based instructional materials that are explicitly aligned with critical thinking indicators to optimize students’ higher-order cognitive skills. Future research should examine the long-term impact of such interventions and explore their applicability across different scientific domains and educational contexts.